Multislice computed tomography (MSCT) of blunt abdominal trauma: incidental findings related to the genitourinary tract - Hassan, Radhiana; Abd. Aziz, Azian; Che Mohamed, Siti Kamariah; Mohd Ralib, Ahmad Rashid (2010)
Background: MSCT is currently the imaging modality of choice in the assessment of hemodynamically stable patients with blunt abdominal trauma. Widespread use of this modality can reveal incidental findings that vary in their importance, from trivial lesions to findings that may alter the management of these trauma patients. Objective: To determine the frequency of incidental findings related to the genitourinary tract at MSCT of blunt abdominal trauma and the effect of these findings on subsequent patient’s management. Material and Methods: MSCT examinations of blunt abdominal trauma in 151 consecutive patients within two years (2008-2009) were retrospectively reviewed. Demographic data and incidental findings related to the genitourinary tract were recorded. The subsequent management of these findings was reviewed from patient’s case note. Results: Twenty one (13.9%) patients had incidental findings related to the genitourinary tract in 151 cases reviewed. Majority of them (n=18) do not require surgical intervention. However, in 3 of these 21 patients, surgical intervention was needed. Conclusion: Incidental findings related to the genitourinary tract in MSCT of blunt abdominal trauma were common. However, those requiring a surgical intervention are rare.